2018
DOI: 10.1039/c8ra02278j
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotungstic acid heterogenized by assembly with pyridines for efficient catalytic conversion of fructose to methyl levulinate

Abstract: A high yield of methyl levulinate (82.5%) was achieved from fructose via a one-pot multi-step conversion process using acidic 3-FPYPW as a heterogeneous catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…After each cycle of the reaction, the catalyst was removed from the reaction system by centrifugation and then washed with 20 mL ethanol for three times, which was finally dried at 80°C for 24 h. The recovered catalyst was utilized directly for the next run under identical reaction conditions. [50][51][52][53][54][55][56] could also be observed for HPyPW and 3-BrPyPW. This result indicated that even HPW was decorated by different organic species; it could well maintain the original HPW cubic basically.…”
Section: Productmentioning
confidence: 73%
See 2 more Smart Citations
“…After each cycle of the reaction, the catalyst was removed from the reaction system by centrifugation and then washed with 20 mL ethanol for three times, which was finally dried at 80°C for 24 h. The recovered catalyst was utilized directly for the next run under identical reaction conditions. [50][51][52][53][54][55][56] could also be observed for HPyPW and 3-BrPyPW. This result indicated that even HPW was decorated by different organic species; it could well maintain the original HPW cubic basically.…”
Section: Productmentioning
confidence: 73%
“…This phenomenon can be attributed to the electrostatic interaction between HPW and ligands [48,49]. Moreover, some unknown diffraction peaks could be observed in 3-BrPyPW and HPyPW, and the possible explanation is that two catalysts will absorb some organic moieties, and this phenomenon has been proved by a previous work [51].…”
Section: Productmentioning
confidence: 74%
See 1 more Smart Citation
“…It can be produced from both C5 carbohydrates and C6 carbohydrates. The acid-catalyzed system conversion of raw biomass such as oil palm fronds, , wheat straw, , bamboo, , paper pulp, , wood chips, , and switchgrass , to LEs was also developed. LEs can be prepared through effective hydrolysis of lignocellulosic biomass into C5/C6 carbohydrates and then undergo catalytic dehydration into LA with furan-derived compounds (furfuryl alcohol (FFA) and 5-HMF) as intermediates and then LA alcoholysis into LE products over the acid catalyst (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the energy density of ethyl levulinate (EL) is approximately 31.2 MJ L -1 , which is similar to that of gasoline (32.4 MJ L -1 ), and obviously higher than that of ethanol (23.5 MJ L -1 ) (Ghosh et al 2018). Much effort has been currently made to determine the efficient synthesis of short-chain levulinate esters, e.g., methyl levulinate (ML) and EL (Fang et al 2018;Liu et al 2018;Lyu et al 2019;Peixoto et al 2021). However, the oxygen contents of ML and EL are relatively high, which leads to high water miscibilities and low heating values (Jia et al 2020).…”
Section: Introductionmentioning
confidence: 99%